Towards victim-centred transitional justice: understanding the needs of families of the disappeared in postconflict Nepal - Robins, Simon (International journal of transitional justice, 2011)
Despite many transitional justice processes claiming to be ‘victim-centred,’ in practice they are rarely driven by the needs of those most affected by conflict. Indeed, in many contexts the views of victims are not sought by those driving the transition. In this article, the needs of a representative sample of 160 families of people disappeared during Nepal’s decade-long Maoist insurgency are studied in an effort to understand what such families seek from the transitional justice process. The study shows that victims emphasize the need for the truth about the disappeared and for economic support to help meet basic needs. Whilst families of the disappeared would welcome justice, this is not their priority. Nepal’s transitional justice process remains still-born and discussions are polarized between a human rights community that prioritizes prosecutions and a political class that seeks to avoid them. An understanding of victims’ expectations of the process can potentially break this deadlock and allow policies to be driven by the needs of those most affected.